Case Report: Adult-onset, chronic, cyclic thrombocytopenia in a Rhesus macaque (Macaca mulatta) after dengue virus vaccination and viral challenge - Frydman, Galit H. (Vet Clin Pathol, 2017)
An 8-year old, male Rhesus macaque (Macaca mulatta) previously used for dengue virus vaccine research with viral challenge, presented with adult-onset, chronic, cyclic thrombocytopenia. Platelet number, morphology and function were evaluated by automated hematology, peripheral blood smears, electron microscopy, flow cytometry, and impedance aggregometry. Bone marrow was evaluated by cytology. Both, serum anti-dengue non-structural protein 1 (NS1) antibodies and anti-platelet antibodies were detected by ELISA. Platelet characterization showed a lack of aggregation to all agonists (ADP, ASP, and collagen), increased activation with increased expression of surface marker (HLA-ABC), and an absence of surface receptor GPIX during clinical episodes of petechiae and ecchymoses, even in the presence of normal platelet counts. Bone marrow aspirates identified potential mild megakaryocytic hypoplasia. All platelet functions and morphologic attributes were within normal limits during clinically normal phases. Presence of anti-dengue NS1 serum antibodies confirmed a positive dengue virus titer 8 years post-vaccination. Based on the history and clinical findings, a primary differential diagnosis for this chronic, cyclic platelet pathology was autoimmune platelet destruction with potential bone marrow involvement.